"Submarine alert" - McDonald, Frank, 1899-1980; Shane, Maxwell, 1905-1983; Arlen, Richard, 1900-1976; Pine-Thomas Productions; Cinetel Films ([Los Angeles, CA] : Pine-Thomas Productions, 1943)
In a devious plot, the FBI unexpectedly fires a loyal radio engineer played by Richard Arlen. Embittered and vengeful at his ill-treatment, he is the ideal bait for a team of Nazi saboteurs who are up to no good. Realizing that he has been set up as part of an FBI plan to capture the Spy ring, the radio engineer works to help catch the Nazis as well as help a fellow engineer who's also been recruited by the saboteurs.
Originally produced as a motion picture in 1943.
Richard Arlen, Wendy Barrie, Nils Asther, Roger Pryor, Abner Biberman.
Cinematographer, Fred Jackman, Jr.; editor, William Ziegler; music, Freddy Rich.
Dubbed into Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 25, 2015).
Keywords: World War, 1939-1945 -- Naval operations -- Submarine -- Drama; Feature films; War films; Spy films; Internet videos; Streaming video